Anisotropic stellar structures in the theory of gravity with quintessence via embedding approach. (April 2021) - Ditta, Allah; Ahmad, Mushtaq; Hussain, Ibrar; Mustafa, G.
Abstract: This work suggests a new model for anisotropic compact stars with quintessence in gravity by using the off-diagonal tetrad and the power-law as, where T is the scalar torsion and and n are real constants. The acquired field equations incorporating the anisotropic matter source along with the quintessence field, in gravity, are investigated by making use of the specific character of the scalar torsion T for the observed stars, , , , and . It is suggested that all the stellar structures under examination are advantageously independent of any central singularity and are stable. Comprehensive graphical analysis shows that various physical features which are crucially important for the emergence of the stellar structures are conferred.